The Impact of Social Media Intensity on Body Dissatisfaction as Mediated by Social Comparison - Oktavia, Nila Audini; Noviekayati, IGAA; Santi, Dyan Evita (Sinergi International Journal of Psychology, 2023)
Social media among teenagers leads to problems with body dissatisfaction caused by the intensity of use, which influences teenagers to compare themselves with the ideal self that is shared on the media. The aim of this research is to determine the role of social media user intensity in body dissatisfaction mediated by social comparison. This research is quantitative research with a correlational model. The subjects in the research were 103 young female students from X senior high school in the Sidoarjo. The data collected was analyzed using the linear regression formula and path analysis to test the mediation hypothesis. The results showed that the intensity of social media use was correlated with body dissatisfaction with a significance value of 0.031 (P<0.05) . The research also found that there is a role of intensity of social media use on body dissatisfaction mediated by social comparison with a t count value greater than t table 14.122 > 1.98.